Secagem da polpa de bacuri: avaliação e estabilidade do pó - Moura, Tháila Pimentel Albuquerque (2022)
The bacuri (Platonia insignis Mart.), fruit of bittersweet flavor and light pulp, has been demonstrating a rise in the brazilian market, belongs to the Amazon biome, but its planting is regional and has seasonal harvest, so not all Brazilian regions have access to the product in natura. Thus, this study aimed to obtain bacuri pulp powder through lyophilization and evaluation of chemical, physical and physical-chemical characteristics, as well as the influence of adjuvants maltodextrin, Arabic gum and albumin. The physical-chemical characteristics of the whole pulp were determined. Bacuri pulp powder was evaluated for moisture, color, hygroscopicity, phenolic compounds, morphology, flow and adsorption containing 20% (m/m) of drying adjuvants. After the evaluation of each adjuvant, the design of Simplex Centroide mixtures was applied in which the best mixture was chosen based on physical and physicochemical analyses in order to evaluate its stability for 90 days. The bacuri pulp presented a high acidity, with 3,21% of citrus acid, 122,27 mg GAE/100g of phenolic compounds and low contents for ash, lipids and fibers. The bacuri powders presented moisture between 2,33 and 2,76%, 182,22 and 386,90 mg GAE/100g of phenolic compound solids and hygroscopicity 6,22 and 6,92%. The adjuvants contributed to a higher luminosity in the bacuri pulp powders in relation to its integral pulp. In the morphological evaluation, the powders presented asymmetric forms, small agglomerations and recesses in their granules, the densities ranged from 287,9 to 433,1 kg/m³ and the friction angles with the wall from 12,2 to 13,55º. The bacuri pulp powders showed acceptable flow, where Carr index and Hausner ratio ranged, respectively, from 23,21 to 25,80% and 1,30 to 1,34. For the isotherms the best model was the BET, with average errors of 5,26% and characteristics of type III. In the mixture design, the junction of Arabic gum and albumin obtained the best results for escoability and conservation of phenolic compounds in powders. In its stability, stable results were observed for moisture, hygroscopicity, small changes in phenolic compounds and low solubility. Therefore, the addition of protein in the polysaccharide gum Arabica enhanced its results to obtain a powder at the industrial level.